Design and testing a bespoke cylinder head pulsating flow generator for a turbocharger gas stand. (15th December 2019) - Vijayakumar, R.; Akehurst, S.; Liu, Z.; Reyes-Belmonte, M.A.; Brace, C.J.; Liu, D.; Copeland, C.
Abstract: Most turbocharger gas stands are designed to map performance under steady flow conditions. However, when connected to an internal combustion engine (ICE), the turbine is exposed to pulsatile flow. In order to enable a full analysis of the unsteady flow and turbocharger performance, it is crucial to quantify unsteady flow effects in the gas stand tests. This paper presents the development and use of bespoke experimental hardware that aims to generate flows in a gas-stand with characteristics similar to that produced by an ICE. This is achieved using a specially modified cylinder head placed between the hot supply and the turbocharger. The device has been designed, manufactured and tested on the gas stand showing its usefulness to study the energy exchange between the engine and the turbine. Testing a turbocharger where a cylinder is deactivated showed large changes in the instantaneous turbocharger speed, pressure and temperature profiles. These unsteady characteristics resulted in a change in the turbocharger behaviour. The insights into unsteady characteristics is expected to contribute to both engine calibration and turbocharger design. It also demonstrates the novelty of the approach in delivering a means to replicate hot, engine-like flow unsteadiness and thereby a wider, more representative data set. Highlights: Various stages from making to testing a novel pulsating flow generator is discussed. Identical engine hardware usage enables proper unsteady flow analysis. The device effectively achieves variable valve actuation and cylinder deactivation. Periods of negative turbine power is generated during the deactivation as it is free-wheeling under its own inertia. Cylinder deactivation shows a distinct turbine and compressor surge behaviour.